Long-term potentiation activates the GAP-43 promoter: Selective participation of hippocampal mossy cells - Namgung, Uk (The National Academy of Sciences of the USA, 1997)
Perforant path long-term potentiation (LTP) in intact mouse hippocampal dentate gyrus increased the neuron-specific, growth-associated protein GAP-43 mRNA in hilar cells 3 days after tetanus, but surprisingly not in granule cells, the perforant path target. This increase was positively correlated with level of enhancement and restricted to central hilar cells on the side of stimulation. Blockade of LTP by puffing dl-aminophosphonovalerate (APV), an N-methyl-d-aspartate (NMDA) receptor blocker into the molecular layer, eliminated LTP-induced GAP-43 mRNA elevation in hilar cells. To determine whether the mRNA elevation was mediated by transcription, LTP was studied in transgenic mice bearing a GAP-43 promoter-lacZ reporter gene. Promoter activity as indexed by Transgene expression (PATE) increased as indicated by blue staining of the lacZ gene product, β-galactosidase. Potentiation induced a blue band bilaterally in the inner molecular layer of the dentate gyrus along the entire septotemporal axis. Because mossy cells are the only neurons in the central hilar zone that project to the inner molecular layer bilaterally along the entire septotemporal axis and LTP-induced activation of PATE in this zone was confined to the side of stimulation, we concluded that mossy cells were unilaterally activated, increasing synthesis of β-galactosidase, which was transported bilaterally. Neither granule cells nor pyramidal cells demonstrated increased PATE or increased GAP-43 mRNA levels. These results and recent evidence indicating the necessity of hilar neurons for LTP point to previously unheralded mossy cells as potentially critical for perforant path LTP and the GAP-43 in these cells as important for LTP persistence lasting days.